The Effect of Nozzle Design Coolant Supply during Machining Automotive Material Al319 - S. Zainal Ariffn; A. M. Efendee; M. Alias; A. A. M. Redhwan; M. N. Muhamed; Ahmad Razlan Yusoff (Advanced Aspects of Engineering Research Vol. 4, 2021)
The thermal effect in adhesive wear and surface finish of Aluminum Alloy 319 (Al319) has a potential problem on the surface roughness, tool wear, and also temperature due to a tendency to melt during cutting process which can cause the formation of built up edge, the inaccuracy of the work pieces, damaged surface due to oxidation and rapid adhesive wear which reduces tool life. The objective of this research is to optimize nozzle coolant system in machining performance of aluminium alloy 319 to achieve a good surface roughness, lower temperature and increased tool wear by selecting suitable machining parameters of cutting speed, depth of cut and feed rate. The variation orifice nozzle sizes used of nozzle from 1.0 mm to 5.0 mm were used with different machining parameters (cutting speed, feed rate and depth of cut) using on the CNC Lathe machine with 2 (two) axes movements, condition and conducted according to the fundamental response surface method (RSM) which is one of an alternative way to minimize the built up edge. By using of such variation combination of sizes of nozzle, the cutting process can be done at high cutting speed and the temperature can be controlled and minimized for the formation of built up edge. The formation of built up edge and thermal can degrade the surface roughness of the work piece. The expected outcome is the smallest of nozzle size used will minimize the thermal effects and reduce temperature which will lead to the reducing built – up edge (BUE) formation. Therefore, better surface roughness, minimized tool wear and low temperature can be achieved. This is due to coolant pointed generator can be directed at one point which dissipated heat from the chips. The compensation between the cutting fluid of the smallest nozzle size and the technique condition in machining process can also be offered to obtain productivity, high quality products, lower cost as well as minimizing the environmental effect (waste coolant produced). Current research is also beneficial to minimize and improve the productivity in machining industries. Consequently, reducing the dependent on the machining operators experience and skill.